Application of Science Explore Books on Earth and Solar System Materials to Improve Understanding of Science Concepts for Grade VII Students : Penerapan Buku Jelajah Sains pada Materi Bumi dan Tata Surya untuk Meningkatkan Pemahaman Konsep Sains Siswa Kelas VII - Roudhlotul Karomah; Ria Wulandari (Universitas Muhammadiyah Sidoarjo, 2024)
Understanding concepts is a very important aspect in learning, especially in science learning where there are many complex concepts and theories so good understanding is needed. The role of educators, methods and teaching materials will be maximized to provide students with a good understanding of concepts. This research aims to determine the increase in students' understanding of science concepts before and after the application of the Science Exploration Book on Earth and Solar System material in class VII by taking samples using a purposive sampling technique. Data collection in this research was in the form of pretest and posttest and analyzed using N-Gain to determine the increase in understanding of concepts that occurred. Based on the research results, there is an increase in the form of differences in the average results of students' pretest and posttest, so it can be concluded that the application of the Science Exploration Book can improve students' understanding of science concepts in Class VII on Earth and Solar System material with a low N-Gain Score category. Highlights: Key role of educators, methods, and materials in science concept understanding. Science Exploration Book enhances Class VII students' grasp of Earth and Solar System concepts. Research shows improvement with a low N-Gain Score category. Keywords: Concept Understanding, Science Exploration Book, N-Gain, Earth, Solar System.